Systematic and ecological study of recent Ostracoda from Al-Faw town, south of Iraq - Al-Meshleb, N.F. (Mesopotamian Journal of Marine Sciences, 2022)
Three boreholes were taken from Al-Faw town, Basrah, South Iraq; at a depth of about 29m, from an area in the flood plain of Shatt Al-Arab River. The cores were constituted essentially of silty clay and clayey silt which predominates the recent sediments. They are characterized by gray dark thin layer of silty clay between 16-17 m. The results indicated the disappearance of fossils in this thin layer due to the absence of water circulation. Twenty-six species of Ostracoda were identified, twelve taxa were recorded for the first time in the study area, these are Macrocyprina decora, Candona magnacauda, Cytherelloidea pracipua, Aurila cf. sp., Loxoconcha certinata, Loxocorniculum cf. sp., L. lilljeborg, Stigymatocythere indica, Neocytheromorpha reticulata, Cypridopsis sp., Cyprideis sp., Hemicytheridea sp., Krith sp. as well as three eco-facies: Fresh water, brackish water and shallow marine Ostracoda.